Primarily Proximal Jejunal Stone Causing Enterolith Ileus in a Patient without Evidence of Cholecystoenteric Fistula or Jejunal Diverticulosis - Houssam Khodor Abtar; Mostapha Mneimneh; Mazen M. Hammoud; Ahmed Zaaroura; Yasmina S. Papas (Case Reports in Surgery)
Stone formation within the intestinal lumen is called enterolith. This stone can encroach into the lumen causing obstruction and surgical emergency. Jejunal obstruction by an enterolith is a very rare entity and often missed preoperatively. To our knowledge, most cases of jejunal obstruction, secondary to stone, were associated with biliary disease (cholecystoenteric fistula), bezoar, jejunal diverticulosis, or foreign body. Hereby we present a rare case report of small bowel obstruction in an elderly man who was diagnosed lately to have primary proximal jejunal obstruction by an enterolith without evidence of a cholecystoenteric fistula or jejunal diverticulosis. This patient underwent laparotomy, enterotomy with stone extraction, and subsequent primary repair of the bowel.